Sustainability Status of Fresh Water White Shrimp (Litopenaeus vannamei) Culture in Glagah District, Lamongan Regency, East Java - Akhmaddin, Derry Bagus; Mahmudi, Mohammad (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2023)
Glagah District is the main area for white shrimp culture with freshwater rearing media in Lamongan Regency, so it is necessary to conduct research to determine the sustainability status of freshwater white shrimp culture in Glagah District. The research locations are in seven villages, namely Soko, Pasi, Margoanyar, Glagah, Jatirenggo, Bapuhbaru, and Karangturi. Sustainability status can be measured by considering five aspects of sustainability which include ecology, economy, social, technology, and institutions. In this study, the analysis was carried out using the RAPFISH (Rapid Appraisal for Fisheries) application with the Multi Dimensional Scaling (MDS) method. This study adopted a quantitative descriptive method, with data collection conducted through a survey. The results of the analysis using the Multidimensional Scaling (MDS) approach to 20 cultivation attributes in the ecological, economic, social, technological and institutional dimensions yielded the following sustainability indexes: 52.23% for the ecological dimension, 58.51% for the economic dimension, 78.47 % for the social dimension, 53.77% for the technological dimension, and 40.46% for the institutional dimension. With an average sustainability index value of 56.69%, it can be concluded that the freshwater white shrimp culture in Glagah District is quite sustainable.